Pengaruh Desain Kemasan Produk Kecantikan Terhadap Minat Beli Konsumen: Pengaruh Desain Kemasan Produk Kecantikan Terhadap Minat Beli Konsumen - Asilmi, Conita Bunga Asilmi (Universitas Negeri Surabaya, 2022)
This study aims to analyze the influence of packaging design on the buying interest of cosmetic consumers. There are five independent variables used in this study, including packaging color, packaging design, packaging material, typeface, and print information. The dependent variable in this study was purchase intent. This study used quantitative research. The population of this study is all consumers of Emina cosmetics in Indonesia. The sampling technique used was purposive sampling and the sample obtained was 100 respondents who met the criteria. The analysis method used in this study is multiple regression analysis. The results showed that packaging color, packaging design, packaging material, typeface, and printed information had a positive and significant effect on the interest in buying beauty products. By knowing the results of this study, marketers are expected to consider packaging attributes as a marketing strategy that can be used to increase company sales.Keyword: packaging attributes, packaging design, packaging material, purchase intent